Zeros of Analytic Continued q-Euler Polynomials and q-Euler Zeta Function - C. S. Ryoo (Journal of Applied Mathematics)
We study that the q-Euler numbers En,q and q-Euler polynomials En,q(x) are analytic continued to Eq(s) and Eq(s,w). We investigate the new concept of dynamics of the zeros of analytic continued polynomials. Finally, we observe an interesting phenomenon of ‘‘scattering’’ of the zeros of Eq(s,w).